1987
DOI: 10.1002/ana.410210310
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spontaneous reperfusion on metabolic function in early human cerebral infarcts

Abstract: Twelve patients were studied within 48 hours of stroke using positron emission tomography to determine cerebral blood flow (CBF), cerebral metabolic rate for oxygen (CMRO2), oxygen extraction fraction, cerebral blood volume, cerebral pH (CpH), and cerebral metabolic rate for glucose (CMRGlc), the last calculated using published normal rate constants (CMRGlc[N]) and those for severe ischemia. In these studies, a cortical region of severe ischemia (I) was outlined, its metabolic and perfusion properties evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(42 citation statements)
references
References 28 publications
3
38
0
1
Order By: Relevance
“…Decreased CBF and aci dotic pH were observed in eight stroke cases within 48 h of onset (Hakim et al , 1987), and alkalotic pH with increased eBF and decreased OEF were re ported in subacute cases (10--34 days after onset) (Syrota et aI., 1983(Syrota et aI., , 1985.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased CBF and aci dotic pH were observed in eight stroke cases within 48 h of onset (Hakim et al , 1987), and alkalotic pH with increased eBF and decreased OEF were re ported in subacute cases (10--34 days after onset) (Syrota et aI., 1983(Syrota et aI., , 1985.…”
Section: Discussionmentioning
confidence: 99%
“…Regions of relative tissue alkalosis were observed in patients with brain tumors (Brooks et aI., 1986), and in patients with stroke 10-19 days after onset (Syrota et aI ., 1983). More recently, regions of tissue acidosis were observed in stroke patients within 48 h of onset (Hakim et al ., 1987). Vol.…”
mentioning
confidence: 99%
“…In nearly one third of adults with AIS of the middle cerebral artery territory, the occlusion clears spontaneously within 24 hours. 29,30 Using positron emission tomography to determine CBF and metabolism, Hakim et al 31 found increased ipsilesional CBF with associated increase in glucose metabolism within 48 hours of stroke onset in one third of patients. In our sample, patients with normal or low perfusion in the infarct tended to have a longer delay between stroke onset and ASL acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the signal as ymmetry in the retia, the collaterals opened during occlusion per sist following clip release, perhaps owing to the presence of an endogenous vasodilator such as aci dosis (Lassen, 1966;Yamaguchi et a!., 1971). These persistent channels are likely to constitute the basis for the postischaemic hyperaemia encountered in experimental and clinical stroke (Sundt and Waltz, 1971;Olsen et a!., 1981;Hakim et a!., 1987).…”
Section: Discussionmentioning
confidence: 99%